2017
DOI: 10.1007/s11571-017-9463-z
|View full text |Cite
|
Sign up to set email alerts
|

A gaze bias with coarse spatial indexing during a gambling task

Abstract: Researchers have used eye-tracking methods to infer cognitive processes during decision making in choice tasks involving visual materials. Gaze likelihood analysis has shown a cascading effect, suggestive of a causal role for the gaze in preference formation during evaluative decision making. According to the gaze bias hypothesis, the gaze serves to build commitment gradually towards a choice. Here, we applied gaze likelihood analysis in a two-choice version of the well-known Iowa Gambling Task. This task requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, to establish the amount of time actually spent gazing at each stimulus, we reckoned it was necessary to add an eye-tracking device to the experimental set-up. For the next 44 subjects, we were able to record manual (keyboard) responses as well as gaze position using Eye Tribe, an eye-tracking device at 60 Hz sampling rate (The Eye Tribe Aps, Denmark); a system with sufficient reliability for present purposes ( Ooms et al, 2015 ; Zommara et al, 2018 ). Thus, the present data set includes a total of 78 subjects: 34 subjects with only manual responses, and 44 subjects with eye-tracking data in addition to the manual responses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to establish the amount of time actually spent gazing at each stimulus, we reckoned it was necessary to add an eye-tracking device to the experimental set-up. For the next 44 subjects, we were able to record manual (keyboard) responses as well as gaze position using Eye Tribe, an eye-tracking device at 60 Hz sampling rate (The Eye Tribe Aps, Denmark); a system with sufficient reliability for present purposes ( Ooms et al, 2015 ; Zommara et al, 2018 ). Thus, the present data set includes a total of 78 subjects: 34 subjects with only manual responses, and 44 subjects with eye-tracking data in addition to the manual responses.…”
Section: Methodsmentioning
confidence: 99%
“…The basic phenomenon of gradually increasing gaze likelihood on the to-be-chosen item was replicated in a variety of forced-choice tasks with a range of stimuli, including human faces ( Simion and Shimojo, 2006 , 2007 ), naturalistic scenes including landscapes, people in daily life, architecture, and animals ( Glaholt and Reingold, 2009 , 2011 ; Schotter et al, 2010 ), abstract visual patterns ( Morii and Sakagami, 2015 ), color cards ( Zommara et al, 2018 ), and images of red-wine bottles and snacks ( Onuma et al, 2017 ). Further evidence suggested that gaze fixation (i.e., effective exposure duration) is the critical factor, independent of gaze shifting ( Nittono and Wada, 2009 ; Bird et al, 2012 ; Gunia and Murnighan, 2015 ; Saito et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…963290-0403). Eye positions were recorded using Eye Tribe, an eye-tracking device at 60 Hz sampling rate (The Eye Tribe Aps, Denmark); a system with sufficient reliability for present purposes 22 , 54 , 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we will refer to this proposal as the "gradualcommitment hypothesis." The evidence of a tight connection between looking and liking was shown to be highly reproducible (including in our own laboratory) in a wide variety of conditions Shimojo, 2006, 2007;Glaholt and Reingold, 2009;Schotter et al, 2010;Bird et al, 2012;Morii and Sakagami, 2015;Zommara et al, 2018). However, several lines of research suggest that the relationship between orienting behavior and preference formation may be complex, as a function of the nature of the stimuli being processed.…”
Section: Introductionmentioning
confidence: 66%